Tourism Development in the Sumenep Archipelago: Policy, Infrastructure, and Stakeholder Synergy - Siska Armawati Sufa; Slamet Riyadi; Agustiawan Djoko Baruno; Garry Brumadyadisty; Irzameingindra Putri Radjamin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Tourism development in the Sumenep Archipelago faces complex challenges due to geographical fragmentation and limited stakeholder synergy. Despite its significant potential in marine and cultural tourism, efforts remain hindered by sectoral coordination, policy misalignment, and uneven infrastructure development. This study investigates how stakeholders communicate and collaborate in tourism development, identifies key obstacles in implementing tourism policies and infrastructure, and explores local community involvement across island districts such as Gili Iyang, Kangean, and Gili Labak. Using a qualitative approach and multi-case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that stakeholder communication is fragmented and project-dependent, lacking a formal collaboration forum. Infrastructure challenges include poor accessibility, weak digital connectivity, and insufficient sanitation facilities. Policy gaps emerge from the disconnect between national frameworks and island-specific spatial and logistical needs. Meanwhile, local communities participate mainly as microeconomic implementers with minimal empowerment, institutional support, or access to capital. The study concludes with a recommendation to establish participatory policies, strengthen local institutions, and facilitate cross-sector collaboration to build an inclusive, adaptive, and sustainable tourism governance model for the Sumenep Archipelago.